Cambridge international diploma for teachers and trainers textbook - Barker, Ian. ([S.l.] : Foundation Books, 2007)
For complete syllabus coverage of the Cambridge International Diplomas. Cambridge International Diploma for Teachers and Trainers Student's book is available from Cambridge University Press India.